The genus Indabracon van Achterberg (Hymenoptera, Braconidae, Braconinae) in China, with description of four new species - Yang Li; Pu Tang; Xue-xin Chen (Journal of Hymenoptera Research, 2020)
The species of the braconid genus Indabracon van Achterberg, 1992 (Hymenoptera: Braconidae, Braconinae) from China are revised and 6 species are recognized, including 4 new species (Indabracon albogilvus sp. nov., I. discolor sp. nov., I. nigricans sp. nov. and I. semicircularis sp. nov.), which are described and illustrated. A key to the Chinese species of the genus Indabracon is provided.